Highly efficient photoluminescence of 2D perovskites enabled by dimensional increasing. (27th January 2021) - Ma, Linlin; Wang, Chao; Chu, Ya; Guo, Yurong; Feng, Xia; Yu, Zhenyi; Zhang, Haoyue; Zhao, Guangjiu
Abstract: Herein, we proposed a dimension-increasing regulation strategy to realize the dimensionality engineering of perovskite from two-dimensional (2D) nanoplates (NPs) to quasi-two-dimensional (Q-2D) nanocrystals (NCs), and successfully prepared 2D (PEA)2 PbBr4 NPs (PEA (phenylethylammonium) = C8 H9 NH3 ), Q-2D (PEA)2 CsPb2 Br7 (1) and (PEA)2 Cs2 Pb3 Br10 (2) NCs. The photoluminescence dynamics changes from 2D (PEA)2 PbBr4 NPs to Q-2D (1), (2) NCs by performing the time-resolved nanosecond transient absorption (NTAS) measurement for our perovskites. Compared with 2D (PEA)2 PbBr4 NPs, we discovered for the first time that the electronic spectral redshift is intrinsic property of Q-2D NCs, which is caused by excitons transition to higher dimensionality. And the photoluminescence quantum yields (PLQYs) of Q-2D (1), (2) NCs is effectively increased from 8.780% to 14.72%, 21.80%, respectively. This directly verifies that Q-2D (1) and (2) NCs have enhanced their interlayer energy transfer capabilities. Moreover, the photoluminescence mechanism of these perovskites is investigated by the NTAS and the time-resolved photoluminescence (TR-PL) spectroscopy. The photophysical process of Q-2D samples exhibits a highly efficient and single photoluminescence pathway. The photoluminescence comes from the radiation recombination of free excitons. The Q-2D samples also have excellent photostability and decay lifetime stability. Our findings advance the research of improving 2D perovskites photoluminescence, and highlight potential of Q-2D NCs for optoelectronic applications.